Tantangan Radikalisme dan Upaya Deradikalisasi Beragama - Sunita Devi; Mahmud Arif (Program Studi Aqidah dan Filsafat Islam, 2022)
Radicalism is a delicate subject with the potential to disrupt the natural order. This study aims to determine the meaning of radicalism, the genealogy of religious radicalism, the factors that cause radical Islam, and deradicalization efforts. This research was a qualitative method with descriptive approach. Based on the research results, it is known that radicalism's teachings and movements are a movement that leads to ideological changes both politically and socially through violence, which is contrary to Islamic values. The challenge of radicalism is overcome by various deradicalization efforts so that it can maintain the nature of Islam itself. Deradicalization is not intended as an attempt to convey a